Integrating Modern Pedagogical Methods to Enhance Creativity and Aesthetic Thinking in Fine Arts Education - Sayfiyeva Ozoda Madamin qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article investigates contemporary pedagogical approaches for enhancing creativity and aesthetic thinking in fine arts education. It focuses on the use of interactive lessons, project-based activities, and digital technologies to develop students’ visual perception, artistic interpretation, and creative skills. The study emphasizes the role of student-centered learning and supportive classroom environments in promoting originality, aesthetic awareness, and innovative artistic expression.